Efek Antibakteri Kombinasi Ekstrak Daun Kelor (Moringa oleifera Lam.) dan Amoksisilin terhadap Staphylococcus aureus dan Escherichia coli secara In Vitro - Setiadi Abdillah Pratama; Tri Widyawati; Muhammad Ichwan; Dian Dwi Wahyuni (Fakultas Farmasi Universitas Pancasila, 2022)
Staphylococcus aureus and Escherichia coli often infect humans and risky cause antibiotics resistance including amoxicillin. This encourages us finding alternative active ingredients: Moringa oleifera leaf. This study evaluated antibacterial activity of combination of Moringa leaf extract (KDK) and amoxicillin (KA) against S. aureus and E. coli in vitro. The research methods with true experimental research with post-test control group design. KDK obtained by maceration. Four concentrations of KDK test materials (20, 30, 40, 50%) and 1 concentration of KA (3 mg/mL). Disc diffusion test method taken and the parameter measured: the diameter of the disc inhibition zone. Data analyzed by One-way ANOVA and further Tukey’s test. KDK+KA against S. aureus (20.77±1.79 – 21.33±1.74 mm)>KDK (11.45±0.21 – 12.45±0.28 mm) or KA (14.50±0.42 mm). KDK+KA against E. coli (15.53±0.71 – 17.87±0.42 mm)>KDK (9.00±0.28 – 10.30±0.42 mm) or KA (13.45±0.35 mm). A significant (p<0.05) was obtained between the combination group (KDK+KA) versus a group (KDK or KA). The combination of Moringa leaf ethanol extract and amoxicillin synergistically effected as antibacterial against S. aureus and E. coli in vitro.